Outreach And Instructions on How to Make Botanical Pesticides In Tresnorejo Village - Saryanto Saryanto; Agung Febri Setiawan; Shifa Dias Azzahra; Novita Irmawati Fatma (Journal Of Human And Education (JAHE), 2026)
The excessive use of synthetic pesticides in the agricultural sector has a negative impact on the environment and human health. This community service activity is aimed at the practice where, after a long harvest season, the community typically plants secondary crops (vegetables and fruits). To explore the potential of papaya leaves, this program is highly relevant to be promoted among the residents of Tresnorejo Village. It is known that papaya leaves contain active compounds such as papain, alkaloids, flavonoids, and other compounds that have the potential to disrupt the feeding and growth of pests. The activity methods included outreach and demonstrations of the preparation process. The botanical pesticide was formulated from a combination of papaya leaves and garlic, which were processed into a spray solution. In addition, the women of the Tresnorejo community provided positive feedback regarding the process of making botanical pesticides, which they considered easy, safe, and economical. Based on the results of the activity, it can be concluded that botanical pesticides have the potential to be environmentally friendly and easy to apply.